Factors Underlying Prophet Ayyub’s Success in Facing Trials: An Analysis of Surah Shad Verses 41–44 in Ibn Kathir’s Tafsir - Suci Sapira Ulfa; Husnel Anwar Matondang (Postgraduate Program of the State Islamic Institute of Palopo, 2026)
This study examines the factors underlying Prophet Ayyub’s success in enduring severe trials based on Ibn Kathir’s interpretation of Surah Shad verses 41–44 and explores their relevance to contemporary Muslim life. Previous studies have generally focused on patience, moral education, and psychological resilience, while the interrelationship between supplication, obedience, and the quality of awwab has received limited attention. This study employed a qualitative, descriptive-analytical library research design using the tahlili method of Qur’anic interpretation. The primary sources were the Qur’an, particularly Surah Shad verses 41–44, and volume seven of Tafsir Ibn Kathir. Relevant books, journal articles, theses, and previous studies served as secondary sources. Data were collected through documentation, validated through source criticism and literature triangulation, and analyzed by describing Ibn Kathir’s interpretation, identifying significant statements, classifying the findings into central themes, and contextualizing their contemporary relevance. The findings reveal three interrelated factors. First, sincere supplication demonstrates Prophet Ayyub’s complete dependence on Allah without turning prayer into a demand. Second, obedience to divine commands represents active effort accompanied by trust in Allah. Third, the quality of awwab reflects his continual return and submission to Allah during both hardship and recovery. These findings demonstrate that Prophet Ayyub’s success was founded not merely on physical endurance or patience, but on a sustained spiritual relationship with Allah. These three factors provide a relevant framework for strengthening Muslims’ spiritual resilience when confronting illness, loss, disaster, and other hardships.